The Factors Affecting the Choice of International Students in Choosing ADA University - Safarli, Vafa (My University, 2015)
This Business Consultancy Project answers questions like why international students choose ADA University for higher education and what can be done by the University to improve recruitment process, the quality of the incoming students as well as their overall academic experience. The document sheds a light to the factors that affects the choice of the foreign students coming to ADA University to study either as a full time undergraduate, graduate or exchange students for one or two semesters.
Business Consultancy Project
Keywords: Business; Education -- Azerbaijan; ADA University -- Azerbaijan.; Azerbaijan -- Universities -- Education